On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: application to human papillomavirus (HPV) - Chekin, Fereshteh; Bagga, Komal; Subramanian, Palaniappan; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Next to graphene nanomaterials, molybdenum disulfide (MoS2) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS2) for the sensitive and selective detection of the L1-major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV culture efficiently, tools based on molecular recognition are becoming of great importance. We developed here an electrochemical sensor for HPV upon covalent functionalization of the electrode with an aptamer Sc5-c3, a RNA aptamer targeted against the HPV-16 L1 protein. Using differential pulse voltammetry (DPV) and an optimized sensor interface, a linear relationship between the peak current density of a redox couple such as [Fe(CN)6]4- and the concentration of HPV-16 L1 proteins in the range of 0.2-2 ng mL(-1) (3.5 pM-35.3 pM) could be reached with a detection limit of 0.1 ng mL(-1) (1.75 pM). Cross-reactivity studies demonstrated high selectivity over potential interfering species such as HPV-16 E6, opening new opportunities of the developed concept for the development of point of care devices. (C) 2018 Elsevier B.V. All rights reserved.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.